User Interface on Smartphone for Elderly Users - Raywadee Sakdulyatham; Somjaree Preeyanont; Rajalida Lipikorn; Rewadee Watakakosol (International journal of automation and smart technology, 2025)
Nowadays, Thai elderly have increasingly been using smartphones to communicate with their families. However, the elderly may have problems using smartphones because most of them normally have visual impairment which result in unclear perception of the screen. The test on how user interface (UI) design of the LINE application affects the elderly when using smartphones shows that the elderly spend more time and make more mistakes than the young adults. The analysis was conducted to find the major factors associated with such problems, and the results show that three components of UI; i.e., font, color, and level of brightness are the major factors that affect how the elderly use their smartphones. In order to confirm the test results, several combinations of font, color, and level of brightness were used to create UI of the simulated LINE application and each UI was used to test with a group of 38 elderly (the age of 60-69) who were told to perform eight different actions on the phone. After further research on UI, it is found that the most appropriate font for Thai elderly is Arial Unicode MS with the size of 16 pt., and the green tone of screen with 75% of brightness level is found to be the most appropriate for the elderly. The test results reveal that the elderly could perform seven actions faster and they made fewer mistakes in six actions. All in all, the test results indicate that the integration of the most appropriate three components can increase the effectiveness of smartphone usage among Thai elderly.